Gastric neuroendocrine tumor: case report and literature review - Fausto, Tarcísio T. de Aguiar (2021)
This study reports the case of a 40-year-old male patient presenting with diarrhea and significant weight loss initiated seven months before admission at the Hospital Geral Roberto Santos. The patient showed no significant changes in the physical examination, and clinical and laboratory investigations were inexpressive. Gastric neuroendocrine neoplasia was diagnosed by endoscopic and anatomopathological studies. Histopathological findings showed a well-differentiated type 2 tumor – a rare neoplasm with a good prognosis. The patient underwent segmental gastrectomy of the gastric body, evolving with clinical improvement of diarrhea. He was discharged from the hospital and is being followed by gastroenterology and endocrinology services.